Asuhan Keperawatan Hipertermia dengan Kompres Hangat pada Pasien Tuberculosis Paru - Putri Hasanah; Deni Susyanti; Muchti Yuda Pratama; Suharto Suharto (Jurnal Riset Hesti Medan, 2022)
Background one of the symptoms of pulmonary tuberculosis is hyperthermia which is the body response to infection process. Tuberculosis sufferers are usually subfebrile, resembling fluenza, but sometimes they can be infected by influenza with body temperature ranging between 38.0 and 38.5oC. The effort made to overcome hyperthermia is by giving warm compresses to reduce fever. Method this is a descriptive research using case study approach that focuses on hyperthermia with warm compresses in pulmonary tuberculosis patient at Tk II Putri hijau Hospital, Medan. Results after nursing interventions in patient I and II with warm compresses on the forehead, axilla, tibia febula, for 4 days, the patients body temperature decreases from 38oC to 37oC. Conclusions it is concluded that there is a nursing problem in patient I and patient II, namely hyperthermia. Suggestions It is expected that the health workers improve their nursing skills in providing nursing care, especially in taking actions to reduce patients fever, so as to reduce its incidence.